Pendidikan Sebagai Upaya Meningkatkan Kreativitas Perempuan Untuk Mendukung Pembangunan Berkelanjutan - Harini, Setyasih; Widhiyoga, Ganjar (Lembaga Penelitian dan Pengabdian Masyarakat, 2019)
Female teachers of SMK Negeri 4 Surakarta have not been able to fill sustainable development, especially in increasing their professionalism in making scientific work. This work is very important in addition to measuring the success of learning as well as to improve the analytical skills of teachers in dealing with problems in the classroom. The problems faced by partners are: (1) lack of understanding and insight into the importance of other libraries that can be used to add teaching material in the teaching and learning process; (2) female teachers are not yet motivated to arrange scientific work as demands that must be met as professionals; (3) not many female teachers take advantage of opportunities and opportunities to develop themselves and increase their creativity as educators to support sustainable development practices; (4) there are still teachers who have not utilized the existence of mass media as partners that can be used to accommodate scientific work to meet the requirements as certified teachers. The targets of the Community Service are as follows: (1) socializing the importance of scientific work as a manifestation of professionalism; (2) holding a meeting to increase the motivation of female teachers in making work of innovation and creativity in order to improve the learning process; (3) provide training in the formulation of opinions based on scientific articles to be uploaded to online mass media. Outputs that can be given through community service are as follows: (1) report on the results of service; (2) making articles for scientific publications that are submitted to the journal of the results of the service; (3) submitting articles to mass media. The method of implementation is through socialization, training, mentoring and motivation. The results of the implementation of the activity showed the enthusiasm and great interest of the female teachers in the socialization and training of the preparation of scientific publications including articles produced to be published in print and online mass media.